2018
DOI: 10.5539/jas.v10n9p333
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Different Soil Management Practices, Soil Fauna and Maize Yield

Abstract: Soil fauna play an important role in ecosystems, and in this context, it is important to better understand how the abiotic and biotic drivers of these organisms interact. We hypothesize that soil fauna are affected by different soil management practices, which has an influence on maize grain yields. The aim of this study was to evaluate the structure of soil fauna under different soil management practices and their associations with maize grain yield. The experiment was conducted in Maranhão, Brazil, in an are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…The higher Shannon diversity in the area with soybean results from the presence of equally distributed groups; dominance was not observed in this area. Shannon diversity values above 1 indicate that the diversity of soil fauna is high and similar values have been reported in other studies (SIQUEIRA et al, 2014(SIQUEIRA et al, , 2016MARTINS et al, 2018).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The higher Shannon diversity in the area with soybean results from the presence of equally distributed groups; dominance was not observed in this area. Shannon diversity values above 1 indicate that the diversity of soil fauna is high and similar values have been reported in other studies (SIQUEIRA et al, 2014(SIQUEIRA et al, , 2016MARTINS et al, 2018).…”
Section: Resultssupporting
confidence: 88%
“…These differences were expected because the area with millet showed greater abundance and dominance of a specific group (Acari -5,772 individuals - Figure 3) and the area occupied by eucalyptus had a dominance of Poduromorpha (2,098 individuals - Figure 3), contributing to the high values of abundance and lower values of richness (Table 3). According to Martins et al (2018), the variations in the number of individuals and taxon of the edaphic fauna is a reflection of the soil occupation system, which provides a greater or lesser contribution of biomass to the system. Studying the diversity of soil fauna in different systems of land use and occupation, Yin et al (2019) concluded that occupation systems with a lower degree of soil disturbance affect the meso and soil macro fauna to a lesser degree.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological diversity was higher for soybean area (Shannon = 2.69), followed by maize (Shannon = 2.42), pasture Shannon = 2.42), eucalyptus (Shannon = 2.08), disturbed cerrado (Shannon = 1.85), millet (Shannon = 1.44) and preserved cerrado (Shannon = 0.73). Studying soil fauna in agroforestry systems, Martins et al (2018) found Shannon values ranging from 1.401 to 1.877. This demonstrates that the diversity values for the present study are superior to those of Martins et al (2018).…”
Section: Soil Faunamentioning
confidence: 99%